2015
DOI: 10.1007/s00300-015-1744-6
|View full text |Cite
|
Sign up to set email alerts
|

Flora and vegetation of Cape Hallett and vicinity, northern Victoria Land, Antarctica

Abstract: Cape Hallett (72°19 0 S; 170°13 0 E) lies at the northern end of the western coastline of the Ross Sea region, and, to date, there appears to be no full description of its terrestrial flora despite its probable importance in understanding links between biodiversity and latitude. Here we present information about lichens and mosses from published papers, herbarium collections and personal surveys for Cape Hallett and seven nearby sites. A total of 59 lichen and 11 moss species are reported for these eight sites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…From a biodiversity and conservation standpoint, Cape Hallett is a significant area (ASPA No. 106) and hosts the richest terrestrial biodiversity in this region of the Ross Sea coastline, with about 46 lichen species, 9 bryophytes and 11 microarthropods [27,28]. Springtails are the dominant microarthropod group, being present at densities two to three orders of magnitude greater than mites [29].…”
Section: Discussionmentioning
confidence: 99%
“…From a biodiversity and conservation standpoint, Cape Hallett is a significant area (ASPA No. 106) and hosts the richest terrestrial biodiversity in this region of the Ross Sea coastline, with about 46 lichen species, 9 bryophytes and 11 microarthropods [27,28]. Springtails are the dominant microarthropod group, being present at densities two to three orders of magnitude greater than mites [29].…”
Section: Discussionmentioning
confidence: 99%
“…The lichen diversity (21 species) of the King George and Ardley islands represent a subset of the 110 species reported by Sancho et al (1999) in their survey of all habitats on Livingston Island. Floristic studies from Victoria Land also revealed a high lichen diversity of 29 (Seppelt et al 2010), 54 (Cannone & Seppelt 2008) and even 59 species (Green et al 2015). There are indications that the species-richness of lichens varies based on latitudes, and hence it was suggested to subdivide Maritime and Continental Antarctica into different phytogeographical regions (Peat et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…2010), 54 (Cannone & Seppelt 2008) and even 59 species (Green et al . 2015). There are indications that the species-richness of lichens varies based on latitudes, and hence it was suggested to subdivide Maritime and Continental Antarctica into different phytogeographical regions (Peat et al .…”
Section: Discussionmentioning
confidence: 99%
“…The primary production of Maritime Antarctic terrestrial ecosystems is extremely low, making autochthonous resources of biogenic substance minimal (Williams 1994;Hopkins et al 2014). Vegetation communities in this region depend largely on marine-derived biogenic substances (main vectors-marine birds and pinnipeds, Green et al 2015). The animal-mediated nutrient deposition creates spatially restricted over-fertilized sites (ornithogenic soils, Tatur et al 1997).…”
Section: Resource Availability-spatial and Temporal Diversity Of Tropmentioning
confidence: 99%
“…Typical for polar coastal oases, the most important limiting environmental factors are water and salinity stress (physiological drought and saline aerosols, Giełwanowska et al 2011). The Antarctic substratum is characterized by instability due to the exfoliation of rock surfaces and cryoturbation of soil and stones (e.g., Green et al 2015;Ochyra et al 2008), together with the presence of permafrost, solifluction or ablation, significantly limiting the development of terrestrial communities ). Specific Antarctic flora and fauna makes the food resources for potential heterotrophic invaders very different from their habitat of origin.…”
Section: Resource Availability-spatial and Temporal Diversity Of Tropmentioning
confidence: 99%